An Investigation of Hearing (250-20,000 Hz) in Children with Endocrine Diseases and Evaluation of Tinnitus and Vertigo Symptoms - Kocyigit,Murat (2020)
Abstract Introduction Despite much advancement in medicine, endocrine and metabolic diseases remain an important cause of morbidity and even mortality in children. Objective The present study was planned to investigate the evaluation of hearing that also includes high frequencies, and the presence and degree of vertigo and tinnitus symptoms in pediatric patients diagnosed with endocrine diseases such as type 1 diabetes mellitus (DM), growth hormone deficiency (GHD), obesity, idiopathic short stature, and precocious puberty Methods The present study included a patient group of 207 children patients diagnosed with endocrine disease (95 males, 112 females; mean age 9.71 years old [range 6-16 years old]) and a control group including 55 healthy children who do not have any kind of chronic disease (26males, 29 females;mean age 9.33 years old [range 6-16 years old]). The subjects underwent a hearing test with frequencies between 250 and 20,000 Hz. The vestibular and tinnitus symptoms were evaluated with the Pediatric Vestibular Symptom Questionnaire. Results Out of 207 patients in the patient group, 5 (2.4%) had hearing loss in pure tones, 10 (4.8%) had it in high frequencies, 40 (19.3%) had tinnitus symptoms, and 18 (8.7%) had vertigo symptoms. A total of 4 out of 207 patients in the study group (1.9%), 2 out of 59 with type 1 DMpatients (3.4%), 1 out of 46 with GHD (2.2%), and 1 out of 43 obesity patients (2.3%) had hearing loss, vertigo, and tinnitus symptoms. Conclusions Our results suggest that some childhood endocrine diseases can cause some changes in the inner ear, although the exact cause is unknown. Perhaps, a detailed hearing and balance examination should be a routine in a child diagnosed with an endocrine disease.We think it is necessary to work on more comprehensive patient groups and tests in the future.